STUDYING THE IMPACT OF DENTAL ANXIETY ON SUCCESS OF TREATMENT AND EXPLORING STRATEGIES TO REDUCE ANXIETY - Shafiqullah Nadi; Dr. Waqar Ali; Dr. Mirza Shayan Baig; Faizan Abdul Hussain Lakhdir; Dr. Sarah Rabbani; Dr Sana Akhtar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This study delves into the intricate relationship between dental anxiety and treatment outcomes while exploring interventions to alleviate anxiety and enhance patient experiences in dental settings. The research, encompassing a diverse cohort of 500 participants aged 18 and above, employed the Modified Dental Anxiety Scale (MDAS) to measure anxiety levels, revealing a mean score of 15 (SD = 3.5), indicative of a moderate level of anxiety. Despite this, participants demonstrated commendable treatment adherence (80%), cooperation during procedures (mean = 4.5, SD = 0.8), and successful treatment outcomes (90% success rate). Patient-reported outcome measures (PROMs) further indicated a high mean satisfaction score of 8.2 (SD = 1.0). Correlation and regression analyses uncovered significant associations between dental anxiety and treatment-related variables, emphasizing the pivotal role of anxiety in shaping patient behavior and influencing treatment success. Integrating these findings with existing literature underscores the imperative for personalized dental care approaches tailored to individual anxiety levels.